Strategi Retensi Karyawan Generasi Z pada Kafe Jagawalungan di Majalengka: Perspektif Manajemen Sumber Daya Manusia - Ganing Indria Maharani (As-Syirkah: Islamic Economic & Financial Journal, 2025)
This study analyzes employee retention strategies for Generation Z at Jagawalungan Café in Majalengka from a Human Resource Management (HRM) perspective. Using a qualitative case study approach, the research identifies strategies such as flexible work arrangements, a family-oriented organizational culture, career development opportunities, digitalization, and participative communication as effective responses to Gen Z retention challenges in the MSME sector. The findings emphasize the importance of a contextual HRM approach that is adaptive to the characteristics of the younger generation and contribute to strengthening retention strategies based on personalization, technology, and sustainable development. This research fills a gap in existing literature on Gen Z retention practices in local MSMEs and provides recommendations for enhancing HRM strategies aligned with generational preferences.